Interview: Cynthia Imogen Hammond and Marc Lafrance on Drawings for a Thicker Skin. (June 2018) - Hammond, Cynthia; Lafrance, Marc
In this interview, Cynthia Hammond sits down with Marc Lafrance in order to discuss the 30-year sketching practice that led to her exhibition, Drawings for a Thicker Skin, in 2012. In this practice, Hammond made small, quick drawings of the clothes she would need for trips or key professional events. As she explains, the drawings were not just essential to knowing what to pack; they were essential to being able to pack. While she never conceived of the practice as art, when invited to exhibit the drawings she found a way to relate this idiosyncratic and private practice to a larger set of ontological concerns. Clothing as a second skin is the key idea here, as Hammond and Lafrance explore what it means to navigate identity, idealized self-image, professional 'passing' and the skin ego.